Influence of Metallurgy and File Design in Micro Crack Formation in Root Canals - An in Vitro Study (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: cracks; controlled memory; dentinal damage; xp endo shaper; hyflex cm; hero shaper; max wire technology